Contextual Blindness: Indonesian Cesarean Section Research Trapped in Narrow Perspectives [Letter] - Muttaqin MZ; Reba YA; Prasetya YY (Dove Medical Press, 2024)
M Zaenul Muttaqin,1 Yansen Alberth Reba,2 Yovian Yustiko Prasetya3 1Department of State Administration, Universitas Cenderawasih, Papua, Indonesia; 2Department of Guidance and Counseling, Universitas Cenderawasih, Papua, Indonesia; 3Department of Guidance and Counseling, Universitas Pancasakti, Tegal, IndonesiaCorrespondence: Yansen Alberth Reba, Department of Guidance and Counseling, Universitas Cenderawasih, Papua, Indonesia, Email yansenreba070189@gmail.com